THE EFFECT OF MARKETING MIX STRATEGY (7P) ON THE EFFECTIVENESS OF SALES OF PT. DUTAMULTI INTIOPTIC PRATAMA, TANJUNG MORAWA - Christina Marsella; Syawaluddin; Mila Asmawiani Okta; Thomas Sumarsan Goh (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2023)
This research was conducted on consumers who work at PT. Dutamulti Intioptic Pratama, Tanjung Morawa. The purpose of this study was to determine and analyze the effect of marketing strategy (7P) on the effectiveness of product sales. The population and sample in this study amounted to 60 people. The sampling technique used is saturated. Data collection techniques are by distributing questionnaires and interviews. Data analysis used multiple linear regression analysis. The conclusion in the study that simultaneously product, price, place, promotion, people, process, and physical evidence have a positive and significant effect on the effectiveness of product sales at PT. Dutamulti Intioptic Pratama, Tanjung Morawa. Partially, place has a positive and significant effect on the effectiveness of selling PT. Dutamulti Intioptic Pratama, Tanjung Morawa. Partially, physical evidence has a positive and significant effect on the effectiveness of selling PT. Dutamulti Intioptic Pratama, Tanjung Morawa, the remaining product, price, promotion, people, and process variables have no effect on the effectiveness of product sales of PT. Dutamulti Intioptic Pratama, Tanjung Morawa The magnitude of the coefficient of determination can be seen from the Adjusted R Square value is: 0.489 which means Product, Price, Place, Promotion, People, Process, Physical Evidence is able to explain Sales Effectiveness of 48.9% while the remaining 51.1% influenced by variables not examined such as: Market Segmentation, Price, Product Quality, and so on.